"Monitorización a pacientes hipertensos ambulatorios tratados con Enalapril del hospital IV Víctor Lazarte Echegaray Febrero - Junio 2007" - Suárez Rebaza, Luz Angélica (2009)
ABSTRACT In the present survey are had using 40 hypertensive patients agreements with enalapril in the hospital IV Víctor lazarte Echegaray during the period February - June 2007, to determine if there is variation significant in the values of blood pressure with the administration of enalapril during his monitoring, which is why a descriptive design was employed, carrying out the domiciliary tracking and in the clinic external of the patients that complied with inclusion and exclusion criteria, taking measures of the values of blood pressure, heart rate, weight, size and that received processing with enalapril 10 mg, dispensed in the drugstore of the hospital. Obtained results show 57.5% and 42.5% of controlled patients and not controlled respectively in the systolic arterial pressure; likewise 95% and 5% of controlled patients and not controlled respectively for the diastolic arterial pressure. On the other hand the variation of the systolic arterial pressure in hypertensive patients outpatient departments was not statistically significant during the study period (p= 0.242). Of obtained results you can conclude that the variation of the blood pressure in hypertensive patients outpatient departments was not statistically significant.